Digital- und Medienpolitik in Parteiprogrammen zur Bundestagswahl 2021; Digital and media policy in party programmes for the German federal parliamentary elections in 2021: How clear and convincing are parties' messages? - Torsten J. Gerpott (Wirtschaftsdienst, 2021)
Vier Parteien - Die Linke, SPD, Bündnis 90/Die Grünen und FDP - haben bis Ende April 2021 den Entwurf ihres Programms zur Bundestagswahl am 26. September veröffentlicht. Wie klar und überzeugend vermitteln Bundestagsparteien ihre Vorstellungen? Die digital- und medienpolitischen Aussagen der Entwürfe werden kritisch analysiert. – – By late April 2021, four parties have published their programme for the German federal parliamentary elections (Bundestag) in September 2021. This article provides a critical comparative review of digital and media policy messages presented in these programmes. The Greens cover current topics in the areas of public service and commercial media large online platform providers and infrastructure roll out for electronic communications both most comprehensively and most vaguely. The digital and media policy statements of the left, social democratic and free democratic parties stick more closely to the respective party's brand.
Keywords: D78; L51; L86; 330